Influence Economic Growth and Percentage of the Unemployed Population to Poverty in Indonesia 2016-2020 - JAYAWARSA, A. A Ketut; DESWARI, Pande Nyoman Natasha; WULANDARI, I.G.A Athina (International Journal of Environmental, Sustainability, and Social Science, 2023)
Focus on the findings of previous studies (gap research) and different perspectives on economic development and factions living unemployed in poverty inform the implementation of this research. Besides that, regardless of the government's effort to combat poverty, there are still problems with research (phenomenon gap) about Indonesia, where the poverty level is still relatively high. The number of people in poverty in Indonesia is not affected significantly by this thing. This research aims to study How the expansion population and the contributing population to poverty interact. Website official Body Center Statistics was used to gather all research data, which was then processed with analysis panel data regression and testing hypothesis (F test, t-test, and coefficient determination). Findings study show that 1) economic growth has a positive and significant impact on poverty, 2) the level of unemployment has a positive and significant impact on poverty, 2) the level of unemployment impact positive and significant on poverty, and 3) economic growth and level of unemployment impact in a way simultaneously to poverty.